Danger in the Canopy. Comparative Proteomics and Bioactivities of the Venoms of the South American Palm Pit Viper Bothrops bilineatus Subspecies bilineatus and smaragdinus and Antivenomics of B. b. bilineatus (Rondônia) Venom against the Brazilian Pentabothropic Antivenom - Sanz, Libia (2020)
We report a structural and functional proteomics characterization of venoms of the two subspecies (Bothrops bilineatusbilineatus and B. b. smaragdinus) of the South American palm pit viper from the Brazilian state of Rondônia and B. b. smaragdinus from Perú. These poorly known arboreal and mostly nocturnal generalist predators are widely distributed in lowland rainforests throughout the entire Amazon region, where they represent an important cause of snakebites. The three B. bilineatus spp. venom samples exhibit overall conserved proteomic profiles comprising components belonging to 11 venom protein classes, with PIII (34–40% of the total venom proteins) and PI (8–18%) SVMPs and their endogenous tripeptide inhibitors (SVMPi, 8–10%); bradykinin-potentiating-like peptides (BBPs, 10.7–15%); snake venom serine proteinases (SVSP, 5.5–14%); C-type lectin-like proteins (CTL, 3–10%); phospholipases A2 (PLA2, 2.8–7.6%); cysteine-rich secretory proteins (CRISP, 0.9–2.8%); l-amino acid oxidases (LAO, 0.9–5%) representing the major components of their common venom proteomes. Comparative analysis of the venom proteomes of the two geographic variants of B. b. smaragdinus with that of B. b. bilineatus revealed that the two Brazilian taxa share identical molecules between themselves but not with Peruvian B. b. smaragdinus, suggesting hybridization between the geographically close, possibly sympatric, Porto Velho (RO, BR) B. b. smaragdinus and B. b. bilineatus parental populations. However, limited sampling does not allow determining the frequency of this event. The toxin arsenal of the South American palm pit vipers may account for the in vitro recorded collagenolytic, caseinolytic, PLA2, l-amino acid oxidase, thrombin-like and factor X-activating activities, and the clinical features of South American palm pit viper envenomings, i.e., local and progressively ascending pain, shock and loss of consciousness, spontaneous bleeding, and profound coagulopathy. The remarkable cross-reactivity of the Brazilian pentabothropic SAB antivenom toward the heterologous B. b. bilineatus venom suggests that the paraspecific antigenic determinants should have been already present in the venom of the last common ancestor of the Bothrops ″jararaca″ and ″taeniatus″ clades, about 8.5 Mya in the mid-late Miocene epoch of the Cenozoic era. The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE partner repository with the data set identifiers PXD020043, PXD020026, and PXD020013.